Semiotic Analysis and Cultural Elements in the Communication Style of Prabowo Subianto and Anies Baswedan in the 2024 Presidential Debate, Third Session - Rafi'i, Rafi'i; Hanifah, Ummy; Ningsih, Titiek Surya; Fairuz, Fara Dilla; Nurjanah, Anna (Dinasti Research, 2025)
This study aims to analyze the political communication styles of two Indonesian presidential candidates, Prabowo Subianto and Anies Baswedan, during the third presidential debate of the 2024 election. Using Roland Barthes' semiotic approach, and using a descriptive qualitative. This study explores the verbal and nonverbal signs presented in the context of Indonesian communication culture. The findings show that Anies Baswedan tends to use a low-context communication style, characterized by rational argumentation, academic diction, and emotional analogies. In contrast, Prabowo Subianto adopts a high-context communication style, rich in symbols, nonverbal expressions, and nationalist narratives rooted in collective culture. These political figures not only demonstrate personal communication strategies but also reflect the cultural heritage embedded in people's perceptions of leadership in Indonesia. Symbols such as